1969
DOI: 10.1039/tf9696502486
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of low-molecular weight poly(ethylene oxide) in water

Abstract: The diffusion coefficients in water of ethylene glycol and several poly(ethy1ene oxides) of low molecular weight have been measured at 15, 25 and 35°C. The activation energies of diffusion are in the range 19-21 kJ mol-' in agreement with published results on more rigid molecules. The Stokes-Einstein diffusion radii increase with temperature probably as a result of conformational changes in the polyoxyethylene chain. After allowing for hydrogen bonding of water molecules at the terminal hydroxyl groups, the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 0 publications
6
25
0
Order By: Relevance
“…G was practically independent of the solute concentration. This is consistent with the finding that the partial specific volume of polyethylene glycol is independent of its concentration [7]. In addition, the partial molal volumes, 17, of the polyethylene glycols were not significantly different from the corresponding values of ~.…”
Section: Viscosity B Coefficientsupporting
confidence: 90%
See 2 more Smart Citations
“…G was practically independent of the solute concentration. This is consistent with the finding that the partial specific volume of polyethylene glycol is independent of its concentration [7]. In addition, the partial molal volumes, 17, of the polyethylene glycols were not significantly different from the corresponding values of ~.…”
Section: Viscosity B Coefficientsupporting
confidence: 90%
“…[3) can be evaluated, provided that the values of K and V for each polyethylene glycol are known. Previous studies [7][8][9] showed that similar polyethylene glycols behave as impermeable spheres in aqueous solution. Hence, the value of K can be taken as 2.5.…”
Section: Viscosity B Coefficientmentioning
confidence: 99%
See 1 more Smart Citation
“…Price (1959) have found that the intrinsic viscosity of PEGS up to a molecular weight of 10 000 is given by the equation The accuracy of this expression may be tested by calculating the diffusion coefficient of PEG 1540. Couper and Stepto (1969) have measured this as 2.173 x cm2 s-' at 25 "C in aqueous solution. The diffusion coefficient was constant between concentrations of 0 and 1.1 g/lOO ml of water.…”
Section: Appendixmentioning
confidence: 99%
“…The root mean square distance between the ends of PEG 4OOO is calculated as 3.40 nm (Couper and Stepto, 1969). If PEG 4OOO can be regarded as a non-freedraining sphere, its diffusion radius may be calculated as 19Onm (Tanford, 1961).…”
Section: The Polymersmentioning
confidence: 99%